Gram Negative Bacteria (Escherichia coli) Win Against Gram Positive Bacteria (Staphylococcus aureus) in The Same Media - Neisya Intan Cahyaningtyas Agung Putri; Ramadhani Ramadhani; Eddy Bagus Wasito (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2021)
Introduction: Biodiversity of the microorganism in Indonesia lead to the large amount of patient with infection. Human can get infected in two different place, with different kind of bacteria that cause the infection. This may lead to bacteremia without knowing which bacteria type whose causing it, either the Gram positive or Gram negative bacteria, whereas the treatment of this two types of bacteria are different. The aim of this study is to determine the doubling time of the Gram positive and Gram negative bacteria when they are grown in the same lesion and the kinds of bacteria that we need to eliminate first.Methods: Staphylococcus aureus and Escherichia coli bacteria were used as samples in this study. Bacterial culture in nutrient broth with 0.5 OD turbidity were mixed then incubated in incubator with 35˚C. Every one hour within 24 hour, 0.01 ml of bacterial culture was taken in serial dilutionover time, varying between 106 – 1012, . It was then planted in nutrient agar plate with droplets technique. After it had been incubated for 24 hours, we counted the Colony Forming Unit per ml (CFU/ml) to time, then the doubling time of the bacteria. The result were then compared between the Staphylococcus aureus and Escherichia coli group.Results: Two tailed t-test result of the doubling time between Staphylococcus aureus dan Escherichia coli was < 0,05 (p=0,000) wich means that there is significant difference of the doubling time between Staphylococcus aureus (24,35 ± 2,23 munites), and Escherichia coli (18,37 ± 0,50 minutes). When grown in the same media, Gram positive bacteria (Staphylococcus aureus) had slower doubling time than Gram negative bacteria (Escherichia coli) as much as 1.32 times.Conclusion: In bacteremia with two possible kinds of bacterial suspect, we need to eliminate the Gram negative bacteria first.